IMPLEMENTASI MAQASHID SYARIAH PADA PELAKSANAAN CSR PT BANK SYARIAH MANDIRI TBK - Shafira Indriani; Suryani Suryani; Siwi Nugraheni (SEKOLAH TINGGI AGAMA ISLAM AL-HUSAIN MAGELANG, 2021)
One of kind the implementation of maqashid sharia in Islamic banking is a Corporate Social Responsibility activity. The priority of CSR activities in the implementation of sharia maqashid aims to create benefits in the surrounding environment by carrying out five aspects as a form of transparency and social responsibility to Allah SWT. The purpose of the research is to determine the impelementation of maqashid sharia of CSR activities at PT Bank Syariah Mandiri Tbk in 2017-2019. This study uses descriptive qualitative method with case study approach. The results of the study showed that PT Bank Syariah Mandiri 2017-2019 achieved the aspect of maqashid sharia refers to 5 aspects, maintaining faith (hifdzu al-din), soul (al- nafs), intellect (hifdzu al-‘aql), prosperity (hifdzu al-nasl), and wealth (hifdzu al-maal). The CSR programs are implemented in the fields of employment, occupational health and safety, stakeholders, fair operational activities, human rights, environment, and community empowerment.